From Nf1 to Sdhb knockout: Successes and failures in the quest for animal models of pheochromocytoma. (5th February 2016) - Lepoutre-Lussey, Charlotte; Thibault, Constance; Buffet, Alexandre; Morin, Aurélie; Badoual, Cécile; Bénit, Paule; Rustin, Pierre; Ottolenghi, Chris; Janin, Maxime; Castro-Vega, Luis-Jaime; Trapman, Jan; Gimenez-Roqueplo, Anne-Paule; et al.
Abstract: Pheochromocytomas and paragangliomas (PPGL) are rare neuroendocrine tumors characterized by a high frequency of hereditary forms. Based on transcriptome classification, PPGL can be classified in two different clusters. Cluster 1 tumors are caused by mutations in SDHx, VHL and FH genes and are characterized by a pseudohypoxic signature. Cluster 2 PPGL carry mutations in RET, NF1, MAX or TMEM127 genes and display an activation of the MAPK and mTOR signaling pathways. Many genetically engineered and allografted mouse models have been generated these past 30 years to investigate the mechanisms of PPGL tumorigenesis and test new therapeutic strategies. Among them, only Cluster 2-related models have been successful while no Cluster 1-related knockout mouse was so far reported to develop a PPGL. In this review, we present an overview of existing, successful or not, PPGL models, and a description of our own experience on the quest of Sdhb knockout mouse models of PPGL. Highlights: Pheochromocytomas and paragangliomas are genetically determined in 40% of cases. PPGL are classified in either the Cluster 1 (pseudohypoxic) or the cluster 2 (MAPK/mTOR). Several Cluster 2-related knockout mouse models are predisposed to pheochromocytoma. No Cluster 1-related knockout mouse models ever developed a pheochromocytoma. Xeno- and allograft models are an alternative to test new therapeutic strategies.